Critical Study of the Word Awliya in the Jamunu Edition of the Ministry of Religion, 2002 and 2019 Translations - Riza Tamami; Moh. Abdul Kholiq Hasan; Ainur Rhain; Kharis Nugroho (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the meaning of awliya’ in the official Indonesian Qur’anic translation published by the Ministry of Religious Affairs (Kemenag) across three editions: the Jamunu Edition, the 2002 Revised Edition, and the 2019 Revised Edition. It focuses on the diversity of Indonesian renderings of awliya’ across Qur’anic verses and investigates the factors underlying these translational variations, particularly in socially sensitive passages such as Q 5:51 (al-Ma’idah). The research employs a qualitative descriptive-analytic approach using library research. Primary data consist of the three Kemenag translation editions, while secondary data include classical and contemporary Qur’anic commentaries, Qur’anic semantic studies, and translation theory literature. Data are analyzed through thematic (maudhu‘i) exegesis, content analysis, and a semantic-contextual approach (Izutsu), taking into account siyaq al-ayah (textual context) and asbab al-nuzul (occasions of revelation). The findings demonstrate that awliya’ is polysemous, and therefore Kemenag adopts context-sensitive renderings such as leaders, protectors/helpers, close loyal friends, and allies. Differences across editions are shaped by (1) linguistic factors (polysemy), (2) verse context, (3) exegetical assumptions informing translation choices, (4) socio-political considerations and the discourse of religious moderation, and (5) an educational orientation toward non-specialist readers. The study concludes that translational variation can enrich readers’ understanding when supported by exegetical literacy, yet it may also generate misleading generalizations if read literally without contextual guidance.